1999
DOI: 10.1021/ic9902020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Ru(II)/Chloro/Hydrido/Carbonyls with Cis Bulky Phosphines:  An Unsaturated Ru(II) Monohydride

Abstract: [RuCl2(CO)2(d t bpe)], d t bpe = tBu2PCH2CH2PtBu2 is synthesized as a mixture of two isomers and is converted to [RuHCl(CO)2(d t bpe)], then [Ru(H)2(CO)2(d t bpe)]. The chloride trans to hydride in [RuHCl(CO)2(d t bpe)] can be replaced by BF4 - or PF6 -, and reaction with NaB(3,5-(CF3)2C6H3)4 gives authentic, five-coordinate [RuH(CO)2(d t bpe)]+, characterized structurally by X-ray diffraction, which reveals the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…25 The hydride complex 12 showed a characteristic triplet (d −7.97) and singlet (d 110.7) in the 1 H and 31 P{ 1 H} NMR spectra respectively. 5 As expected, there was no evidence for bound triflate ( 19 F NMR). The molecular geometry of 12 was established unequivocally by X-ray crystallography.…”
Section: Water-gas Shift Chemistry Of 8 To Afford [Ru(d T Bpe)(co) 3 ...supporting
confidence: 62%
See 2 more Smart Citations
“…25 The hydride complex 12 showed a characteristic triplet (d −7.97) and singlet (d 110.7) in the 1 H and 31 P{ 1 H} NMR spectra respectively. 5 As expected, there was no evidence for bound triflate ( 19 F NMR). The molecular geometry of 12 was established unequivocally by X-ray crystallography.…”
Section: Water-gas Shift Chemistry Of 8 To Afford [Ru(d T Bpe)(co) 3 ...supporting
confidence: 62%
“…The dichloride complex, [Ru(d t bpe)(CO) 2 Cl 2 ] (2), has been reported by Caulton and co-workers to be formed as part of an inseparable mixture containing all-cis and trans-(CO) 2isomers upon refluxing [Ru(CO) 2 Cl 2 ] 2 with d t bpe under a slow flow of CO. 5 Assignment of all stereochemistries was based upon 31 P/ 13 C NMR spectroscopy and IR data. During one of our first efforts to prepare this mixture, we were able to crystallise the more unusual trans-dicarbonyl isomer (unusual on the grounds of the two p-acceptor ligands occupying trans positions) 6 and confirm the geometry unambiguously through X-ray crystallography, as shown in Fig.…”
Section: Metathesis Reactions Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Elemental analysis of the solid and 31 P NMR confirmed that the product was [Ru(l-Cl)Cl(CO) 2 -(detp)] 2 . Although halide-bridged dimers containing small phosphines have been previously reported [38,[50][51][52][53] examples of ruthenium carbonyl halidebridged dimers containing bulky phosphanes are less common [54][55][56].…”
Section: Non-chelated Complexesmentioning
confidence: 99%
“…The use of boiling methanol, instead of 2-methoxyethanol, as a solvent yielded the alltrans isomer instead of the cis-cis-trans one [37]. The thermodynamically less stable all-trans isomer 6, due to the mutual competition of both CO ligands for the electronic charge of the metal [38], can therefore be obtained using methanol as solvent.…”
Section: Hydride-carbonyl Complexesmentioning
confidence: 99%